The savvy cook - Hossack, Izy (Mitchell Beazley, 2017)
For those cooking for themselves for the first time, or for anyone who wants the weekly budget to go a bit further without sacrificing flavor, The Savvy Cook has all the answers. Although many of the recipes are gluten-free and/or vegan, this book is not about health fads, "antioxidants" or obscure ingredients; it's about honest, nourishing and delicious cooking that will make you glow both inside and out! Izy's delicious recipes include Berry Oat Smoothie Boxes, Butternut Squash Pilaf with Garlic-tahini Dressing, Sweet Potato and Salmon Cakes, and American Pancakes. With features that include menu plans, sneaky ways to cut down on meat and giving last-night's leftovers a make-over, this collection of nourishing and totally delicious recipes will be kind to your body, wallet and leisure time.